Interpretive Journalism Perspective on Brewing Contextualized Citation and Referencing Practices in African Scholarship - Okhueleigbe, Osemhantie Amos (Communicate: Journal of Library and Information Science, 2025)
This qualitative study, titled "Interpretive Journalism Perspective on Contextualized Citation and Referencing Practices in African Scholarship," explored the challenges of citation practices in African scholarship and proposed contextually relevant frameworks honoring local naming conventions and knowledge systems. Anchored on Social Constructivism and Critical Theory, the study employed document analysis, meta-analysis, and thematic/content analysis through a systematic review of peer-reviewed articles, policy documents, and case studies. The findings highlighted the limitations of existing citation frameworks in capturing African communal knowledge, underscoring the need for transformation. To address this, the study recommended integrating indigenous knowledge systems to recognize local skills and practices, prioritizing collective authorship representation to acknowledge community contributions, implementing educational initiatives to empower scholars in culturally relevant citation practices, and incorporating local languages and cultural contexts to enhance indigenous knowledge visibility. The study concluded that embracing indigenous citation practices will foster a more equitable academic landscape, recognizing and valuing diverse knowledge systems. The research contributes to the development of contextualized citation practices, enriching scholarship by celebrating diverse knowledge systems and promoting a richer understanding of local knowledge and its global relevance.